Japan in crisis. Essays on Taish ̄democracy. Ed. by B.S. Silberman and H.D. Harootunian. Contributors: G. Bernstein, J.B. Crowley, A. Iriye [a.o.] (Princeton University Press, 1974)
With index and tabs.